Trend starts here: perks on self-esteem among Filipino undergraduate TikTok users - Sia, Danneth Krystel; Fabi, Nhereene; Maceda, Renier Aron; Udtuhan, John Herbert; Nacionales, Joseph; Claridad, Norberto (Journal of Language, Literature, Social and Cultural Studies, 2023)
The emergence of the TikTok application represents noteworthy phenomenon in the realm of social media. It became an avenue for self-expression, business, awareness-raising, and entertainment (Insider Intelligence, 2022). This indicates that more individuals will continuously be engaged by this app, especially undergraduate TikTok users, who are usually exposed (Adawiyah, 2020). This stimulates the researchers in identifying the perks of the TikTok app for the self-esteem of Filipino undergraduate students along with the distinct features of the platform. This study employed a qualitative research design through interpretative phenomenological analysis (IPA) developed by Smith et al. (2009). Using the purposive convenience sampling, 24 participants were interviewed, in person and via email. The responses of the participants underwent thematic approach of Braun and Clarke (2019). Rigorous condensation of the transcript led in shaping four distinct themes (1) engagement of undergraduate TikTok users on the application, (2) meeting the undergraduates TikTok users’ purpose for a sense of fulfillment. (3) improvement rendered by the TikTok application o undergraduates’ qualities and abilities and (4) interactive and production features as a source of self-esteem advancement. Various practical recommendations were further elaborated at the end of the study.